2020
DOI: 10.1016/s0140-6736(20)30537-7
|View full text |Cite
|
Sign up to set email alerts
|

Thulium laser transurethral vaporesection of the prostate versus transurethral resection of the prostate for men with lower urinary tract symptoms or urinary retention (UNBLOCS): a randomised controlled trial

Abstract: Summary Background Transurethral resection of the prostate (TURP) is the standard operation for benign prostatic obstruction. Thulium laser transurethral vaporesection of the prostate (ThuVARP) is a technique with suggested advantages over TURP, including reduced complications and hospital stay. We aimed to investigate TURP versus ThuVARP in men with lower urinary tract symptoms or urinary retention secondary to benign prostatic obstruction. Methods In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…The remaining 91 papers were further assessed to exclude studies with the same population and different follow‐up. Finally, 25 studies including 1 RCT parallel study, 11 prospective single arm study, and 13 retrospective studies, were identified for meta‐analysis 12–36 . Figure 1 shows the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 91 papers were further assessed to exclude studies with the same population and different follow‐up. Finally, 25 studies including 1 RCT parallel study, 11 prospective single arm study, and 13 retrospective studies, were identified for meta‐analysis 12–36 . Figure 1 shows the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…HoLEP has been highly scrutinized with level 1 evidence to suggest that it provides at least equivalent if not better improvement A recent RCT also failed to demonstrate any difference in efficacy or safety between TURP and Thulium laser vaporesection of the prostate (ThuVARP). 162 The retreatment rate of HoLEP has been reported at 0% in a long-term outcome study of an RCT with 7 years of follow-up, 163 compared with 1%-2% per year when treated with monopolar TURP. 1…”
Section: Efficacy and Durabilitymentioning
confidence: 99%
“…Of note, only 24% of patients without sexual dysfunction at baseline developed sexual dysfunction 12 months post-surgery. 12 …”
Section: Introductionmentioning
confidence: 99%